Notes on Salvia subgenus Calosphace section Macrostachyae (Lamiaceae) from Ecuador with a new record - Fragoso-Martínez, Itzi; Martínez-Gordillo, Martha; Uría, Rolando; Salazar, Gerardo A.; Peñafiel, Marcia; Tobar, Francisco (Phytotaxa, 2021)
Salvia alata is reported as new record for Ecuador. This species belongs to S. sect. Macrostachyae, thus an updated identification key to species of this section is provided. The descriptions of Salvia alata and the species most morphologically similar to it (Salvia speciosa) are complemented with new information and photographs taken in the field. Salvia alata is distributed in Ecuador and Peru and can be distinguished from Salvia speciosa by its pilose vegetative organs, flowers with white stamens and styles, and mericarps with a deltoid apex. On the other hand, Salvia speciosa is endemic to Peru, and it has glabrescent vegetative organs, flowers with burgundy to deep purple stamens and styles, and mericarps with a bifurcate apex.